2018
DOI: 10.1002/2017jd027968
|View full text |Cite
|
Sign up to set email alerts
|

Directional Absorption of Parameterized Mountain Waves and Its Influence on the Wave Momentum Transport in the Northern Hemisphere

Abstract: The directional absorption of mountain waves in the Northern Hemisphere is assessed by examination of horizontal wind rotation using the 2.5° × 2.5° European Centre for Medium‐Range Weather Forecasts ERA‐Interim reanalysis between 2011 and 2016. In the deep layer of troposphere and stratosphere, the horizontal wind rotates by more than 120° all over the Northern Hemisphere primary mountainous areas, with the rotation mainly occurring in the troposphere (stratosphere) of lower (middle to high) latitudes. The ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…On the other hand, the mean value of both distributions is approximately equally justifying the utilization of composites from spatially averaged OGWD for dynamical analysis. The magnitude of higher-order moments (especially kurtosis as a measure of the "tailedness" of the distributions) is another measure of the intermittency (Zel'Dovich et al, 1987;Mahrt, 1988). The spatially averaged OGWD represents still a highly intermittent forcing in the LS.…”
Section: Composite Analysismentioning
confidence: 99%
“…On the other hand, the mean value of both distributions is approximately equally justifying the utilization of composites from spatially averaged OGWD for dynamical analysis. The magnitude of higher-order moments (especially kurtosis as a measure of the "tailedness" of the distributions) is another measure of the intermittency (Zel'Dovich et al, 1987;Mahrt, 1988). The spatially averaged OGWD represents still a highly intermittent forcing in the LS.…”
Section: Composite Analysismentioning
confidence: 99%
“…Recently, Xu et al (2018) designed an OGW parameterization scheme taking into account the directional absorption of OGWs (hereafter, the X18 scheme). Offline evaluation using reanalysis data in X18 showed that the scheme can produce weaker (stronger) OGWD in the lower stratosphere (upper stratosphere and lower mesosphere) because directional absorption tends to a transfer of wave breaking to higher levels.…”
Section: Introductionmentioning
confidence: 99%
“…These differences may be explained by the fact that the parameterization of OGWs is tuned to represent a missing drag in the SH resulting in the overestimation in the NH (McLandress et al, 2012). Using horizontal propagation and directional absorption of OGWs in the parametrization may bring the GWD in the middle latitudes closer to observations (Xu et al, 2017(Xu et al, , 2018, particularly considering that GW momentum fluxes as derived from satellite observations may be underestimated (Trinh et al, 2015;Ern et al, 2018). Still, the high bias in the NH emerges as deficiency of current GW parameterizations in GCMs https://doi.org/10.5194/wcd-2020-21 Preprint.…”
Section: Discussionmentioning
confidence: 99%